2016
DOI: 10.1177/1367006915609235
|View full text |Cite
|
Sign up to set email alerts
|

Second language influence on first language motion event encoding and categorization in Spanish-speaking children learning L2 English

Abstract: Studies show cross-linguistic differences in motion event encoding, such that English speakers preferentially encode manner of motion more than Spanish speakers, who preferentially encode path of motion. Focusing on native Spanish speaking children (aged 5;00-9;00) learning L2 English, we studied path and manner verb preferences during descriptions of motion stimuli, and tested the linguistic relativity hypothesis by investigating categorization preferences in a non-verbal similarity judgement task of motion c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 31 publications
1
32
1
Order By: Relevance
“…Five-to 6-year-olds were exposed to 8 hours/week of English classes whereas this amount was 16 hours/week for 7-to-9year-olds. In a further study Aveledo and Athanasopoulos (2016) replicated Aveledo (2015) and got the same results. The findings of both studies converge with the findings of the present study as they show that more L2 hours in school enhances the likelihood of L2 effects on children's motion descriptions in L1.…”
Section: Discussionsupporting
confidence: 56%
“…Five-to 6-year-olds were exposed to 8 hours/week of English classes whereas this amount was 16 hours/week for 7-to-9year-olds. In a further study Aveledo and Athanasopoulos (2016) replicated Aveledo (2015) and got the same results. The findings of both studies converge with the findings of the present study as they show that more L2 hours in school enhances the likelihood of L2 effects on children's motion descriptions in L1.…”
Section: Discussionsupporting
confidence: 56%
“…Consistent with studies of monolingual speakers, bilingual cognition research also presents mixed and inconsistent results. In one such study, Aveledo and Athanasopoulos (2016) examined both motion encoding patterns and categorization patterns of Spanish–English bilingual children. They demonstrated that no significant differences were found between monolingual and bilingual children in their categorization, suggesting that language did not mediate their non-verbal performance.…”
Section: Motion Event Construal In Bilingualsmentioning
confidence: 99%
“…So far, studies in these two lines of research have rigorously explored their questions of interest, but mostly in separate studies. With the exception of few studies (e.g., Aveledo & Athanasopoulos, 2016; Filipović, 2011), there has been very little attempt to address linguistic relativity and conceptual transfer together in a single study to garner a holistic understanding of how L2 users speak and think about a certain concept. To obtain a fuller picture of how language and thought interact within bilingual adults, the present study examined verbal and non-verbal behaviors of Korean–English sequential bilinguals in the domain of motion events.…”
Section: Introductionmentioning
confidence: 99%
“…We are currently examining the narratives in Chinese collected from the same bilingual participants in comparison with their Chinese-speaking monolingual peers. If parallel influences of English on Chinese and Chinese on English were found, we would have another case of bidirectional cross-linguistic influence (Aveledo & Athanasopoulos, 2016; Jarvis & Pavlenko, 2008).…”
Section: Discussionmentioning
confidence: 99%